2020
DOI: 10.1167/tvst.9.8.34
|View full text |Cite
|
Sign up to set email alerts
|

A Reflectivity Measure to Quantify Bruch's Membrane Calcification in Patients with Pseudoxanthoma Elasticum Using Optical Coherence Tomography

Abstract: Progressive calcification of Bruch's membrane (BM) causes considerable visual morbidity in patients with pseudoxanthoma elasticum (PXE). Since calcification is hyperreflective on optical coherence tomography (OCT), our aim was to measure BM calcification with OCT imaging. Methods: Case-control study with 45 patients with PXE under 40 years (range, 11-39) and 25 controls (range, 14-39). Spectralis HRA-OCT imaging consisted of seven macular B-scans with 250-μm spacing. Retinal segmentation was performed with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…The categorical classification of the length of angioid streaks leads to loss of information when compared to a continuous measure. Other approaches, including quantification of Bruch's membrane reflectivity on macular OCT-scan [36] and measurement of the border of peau d'orange on 30 • NIR imaging are under development. However, these measurements are only possible in the early stage of disease when there is no macular degeneration yet [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The categorical classification of the length of angioid streaks leads to loss of information when compared to a continuous measure. Other approaches, including quantification of Bruch's membrane reflectivity on macular OCT-scan [36] and measurement of the border of peau d'orange on 30 • NIR imaging are under development. However, these measurements are only possible in the early stage of disease when there is no macular degeneration yet [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches, including quantification of Bruch's membrane reflectivity on macular OCT-scan [36] and measurement of the border of peau d'orange on 30 • NIR imaging are under development. However, these measurements are only possible in the early stage of disease when there is no macular degeneration yet [36,37]. The length of angioid streaks is the first measure that allows for semi-quantitative measurements in nearly all PXE patients, including those with end-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an OCT-based quantification for BM calcification in patients with PXE was proposed. 32 However, further research and external validation is warranted before this is suitable as a biomarker in normal subjects.…”
Section: In This Study We Developed a Measure For The Extentmentioning
confidence: 99%
“…Ideally, such a biomarker should be able to detect change over time in pre-atrophic stages of the disease. Risseeuw et al 15 have recently shown that BrM calcification can be measured in vivo based on the increased reflectivity of the RPE–BrM retinal band on optical coherence tomography (OCT). However, with current imaging and image analysis techniques, the reproducibility of reflectivity metrics is limited.…”
mentioning
confidence: 99%
“…However, with current imaging and image analysis techniques, the reproducibility of reflectivity metrics is limited. 15 …”
mentioning
confidence: 99%